The Disputes of South China Sea From International Law Perspective - Surya Wiranto; Hikmahanto Juwana; Sobar Sutisna; Kresno Buntoro (Postgraduate of Jayabaya University, 2015)
Disputes in the South China Sea (SCS) occur due to the seizure of mari- time regions of Spratly and Paracel islands, the regions which are rich in natural resources of oil and gas. Indonesia is not a claimant state to the features in SCS, but Indonesia has a vital national interest to the jurisdiction of waters of the exclusive economic zone (EEZ) and the continental shelf which overlaps with claims 9 dashed lines of PRC. In analyzing and resolving these disputes, the writer uses theory of law- based state as a grand theory, the theory of international law as a middle range theory, and theory of conflict resolution as an applied theory. The method is a normative legal research. The legal materials are collected based on the identifted list of problems/issues and are assessed according to the classiftcation of the problems. The legal materials are deductively managed to draw conclusions from the problems encountered, and are further analyzed to solve these problems. Conflict resolution to maritime territorial dispute can be achieved by legal means. The dispute settlement by legal means can be done through bilateral, multilateral, arbitration, to the International Court of Justice, while the dispute resolution through CBMs can be achieved through dialogue in international fora by applying the formula 6 + 4 + 2 or 6 + 4 + 1 + 1, and by conducting survey and research cooperation in the fteld of maritime.